Analisis Pengaruh Pertumbuhan Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Gowa Motor Group Yang Terdaftar Di Bosowa Automotive - Ady Kurnia; Ramli Toalib (Fakultas Ekonomi Universitas Indonesia Timur, 2020)
This study aims to determine the effect of company growth on firm value in Gowa Motor Group companies registered with Bosowa automotive. The independent variable in this study is company growth, the dependent variable is the value of the company. The population of this study is the Gowa Motor Group company registered in Bosowa automotive in the 2014 to 2017. research methods of determining the sample using the purposive sampling method, with several predetermined criteria, the number of samples was 4 companies. The data analysis method used is multiple linear regression with a significance level of 0.05. Based on the results of data analysis using partial test (t-test) the variable company growth has a significant positive effect on firm value with a significance value of 0.003. The results of the accuracy test of the model obtained a calculated F value of 17.728 with a significance value of 0,000. Regression analysis produces Adjusted R of 0.770 or 77.0%. This study means that the firm's value variable can be explained by the company's growth variable, at 77.0%, while the remaining 23.0% is explained by other variables outside the model.